RELAÇÃO ENTRE AS TÁTICAS DE INFLUÊNCIA E OS RESULTADOS DA LIDERANÇA NA ENFERMAGEM - SANEMATSU, LAUDELINO SIQUEIRA AMARAL (2017)
In the last two decades, the Brazilian scientific production evidences a lack of indicators of the effect of leadership on the organization’s results. Thereby, the present study aimed: to identify, to analyze, to evaluate and to comprehend a relationship between the tactics of influence used by leaders and the results achieved by leadership, more specifically, Extra Effort of the led, Leader Effectiveness and Satisfaction with the Leader. The study was accomplished in the context of nursing, which can be considered a complex management environment. The nurse has insufficient training in the topic of leadership, although as national curricular guidelines of the nursing graduate course, as one of the objectives in this graduation is to provide the professional with competence to lead. The method used for the elaboration of this project was adopted in a quantitative approach with descriptive definition, using survey with printed questionnaires. The target audience for the research was on nursing professionals’ area with at least six months' experience and who, as hierarchical superior, the nurse. The sample consisted of 309 valid respondents, from the interior of the state of São Paulo, acting in the public, private and third sector. The SPSS software v.19 (Statistical Package for the Social Sciences) was used for the data processing and for the calculations and validations of the statistical tests was used the multivariate analysis technique of structural equations modeling by the partial least squares method (PLS- PM Partial Least Squares Path Modeling), with SmartPLS 3.0.M3 software. As a result, this project corroborates with several other studies of Brazilian authors in the context studied under the topic of leadership and, in the end, proposes a table of which influence tactics to use for the result of the one intends to achieve in a complex management context. In order to obtain Extra Effort from the led, the tactic that presented the greatest impact was Consultation. Already to be recognized the Leader Effectiveness or to get the Satisfaction with the Leader, the tactics with greater impacts were Rational Persuasion and Collaboration. However, other tactics of influence act in an additional way, according to the results of the present research, for the three dependent constructs. It concludes the leaders that use the Transformational leadership style achieve Extra Effort from their led and leaders who use the Transactional leadership style obtain the recognition of Leadership Effectiveness and Leadership Satisfaction in the respondents' perception. In addition, moderation and multi-group analyzes were carried out, in order to reveal other conclusions involving the demographic data of the respondents.